Pain Prevalence, Localization, and Intensity in Adults with and without COPD: Results from the Danish Health and Morbidity Survey (a Self-reported Survey) - Hansen, Jeanette (Int J Chron Obstruct Pulmon Dis, 2020)
INTRODUCTION: Pain is a clinical complication to chronic obstructive pulmonary disease (COPD) that interferes negatively with physical activity level (PAL), quality of life (QOL) and pulmonary interventions. Yet, research in pain characteristics including prevalence, localization, and intensity in people with COPD are sparsely researched. AIM: To investigate self-reported pain prevalence, localization and intensity of pain in people with and without COPD, and to investigate the association between pain intensity and PAL among participants with COPD. METHODS: Data were derived from the Danish Health and Morbidity Survey in 2017. The study population was restricted to individuals aged ≥35 years. Data included pain intensity assessed on the Numeric Rating Scale (NRS) and localization, PAL, QoL, sleep disturbance, comorbidities, sociodemographic and behavioral factors. RESULTS: In all, 528 participants with COPD and 8184 participants without COPD (51% females, mean ±SD age 67.1±11.4 years) were analyzed. Pain prevalence within the past 14 days was significantly higher in participants with COPD vs nonCOPD (72.7% vs 57.7%, p<0.001) and mainly located in the limbs, thorax, and lower back. COPD was associated with the prevalence of chronic pain (≥6 months) (OR: 2.78, 95%CI: 2.32; 3.34, p<0.001). Participants with COPD reported a higher pain intensity compared to those with nonCOPD with a mean difference of 1.04 points (95%CI: 0.75; 1.32, p<0.001) on the NRS. In the adjusted multiple logistic regression analysis, pain intensity was negatively associated with odds of being physical active (OR: 0.72, 95%CI: 0.61; 0.85, p<0.001). CONCLUSION: Pain is more prevalent in people with self-reported COPD. After adjustment for age and gender, COPD was associated with an elevated pain intensity. Sleep disturbance and multimorbidity had the most pronounced impacts on pain intensity in the multiple linear regression model. In participants with COPD, increased pain intensity was negatively associated with being physically active.